2011
DOI: 10.1017/s1751731110002090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breed and age on the performance of crossbred hill ewes sourced from Scottish Blackface dams

Abstract: The aim of this study was to evaluate the effects of age and breed on the reproductive performance and lamb output of crossbred hill ewes relative to purebred Scottish Blackface (BF). BF ewes were compared alongside Swaledale (SW) 3 BF, North Country Cheviot (CH) 3 BF, Lleyn (LL) 3 BF and Texel (T) 3 BF ewes on six commercial hill farms across Northern Ireland, on which all the ewes were born and reared. Ewes were mated to a range of sire breeds, balanced across breeds, for up to five successive breeding seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 28 publications
3
32
1
3
Order By: Relevance
“…Selection of crossing sire breed to produce prolific females for hill flocks may be important. SW 3 BF ewes tended to remain in the flock longer than LL 3 BF even though both breeds had similar levels of prolificacy (Annett et al, 2010). Therefore, ewes sired by prolific hill breed types such as SW may be more appropriate for hill flocks than those sired by prolific lowland breeds.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Selection of crossing sire breed to produce prolific females for hill flocks may be important. SW 3 BF ewes tended to remain in the flock longer than LL 3 BF even though both breeds had similar levels of prolificacy (Annett et al, 2010). Therefore, ewes sired by prolific hill breed types such as SW may be more appropriate for hill flocks than those sired by prolific lowland breeds.…”
Section: Discussionmentioning
confidence: 93%
“…In agreement with McGloughlin and Curran (1969), the primary reason for culling was due to infertility (0.408) and was followed by udder abnormalities (0.227), poor teeth condition (0.188), vaginal prolapse (0.069) and poor body condition (0.040). The relative rate of culling due to infertility was lower in LL 3 BF and T 3 BF compared with CH 3 BF and mirrors their higher prolificacy (Annett et al, 2010). Waterhouse et al (1992) reported increased survival in BF ewes treated with Fecundin R (Glaxo Animal Health, UK) to boost prolificacy.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations